Percutaneous nephrolithotomy under spinal anaesthesia: a series of 100 cases - A. A., Abraham; Das, Vishnu (International Journal of Research in Medical Sciences, 2016)
Background: PCNL was introduced by Fern Storm and Johansson in 1976 and further developed in the following years. Till 1988 all the procedures were done under general anaesthesia (GA). This study is to determine if PCNL can be done under spinal anaesthesia with satisfaction to the patient, surgeon and anaesthesiologist and to find out if there are any complications. Methods: PCNL was introduced by Fern Storm and Johansson in 1976 and further developed in the following years. Till 1988 all the procedures were done under general anaesthesia (GA). This study is to determine if PCNL can be done under spinal anaesthesia with satisfaction to the patient, surgeon and anaesthesiologist and to find out if there are any complications. Results: In two patients, spinal anaesthesia failed to act. They were converted to general anaesthesia. Two patients who complained of discomfort in the prone position were reassured and given increments of Midozolam 0.5 mg. Three patients had developed bleeding.98 patients underwent surgery under spinal anesthesia with good patient satisfaction. There were no major complications. Conclusions: PCNL can be done under spinal anesthesia to the satisfaction of the patient, surgeon and anesthesiologist.